Pharmacological treatment of cocaine/crack addiction: analysis of pharmacotherapy in chemically dependent patients (Research, Society and Development, 2022)
Dependence caused by cocaine use represents a public health problem in several countries. Despite its high potential to cause dependence, there is still no clinical protocol for pharmacological treatment. However, from positive results, some clinicalstudieshavealreadybeendevelopedwiththepurposeofidentifyingpharmacologicaltherapies in order to minimize the desire to consume the substance. The pharmacological treatment of addictions consists of psychotropic drugs, which are controlled drugs that act on the Central Nervous System. These medications contribute to their duction of drug withdrawal symptoms, in addition to symptoms of any psychiatric comorbidities that the patient may present. In this sense, pharmacotherapy acts in the treatment of chemical dependence, complementing other activities that seek to improve the quality of life of patients. This study aimed to carry out a bibliographic survey on the pharmacological treatment of cocaine/crack addiction, taking into account the analysis of pharmacotherapy in chemically dependent patients. For this, publications available in the PUBMED, LILACS, and VHL databases were used for the period from 2012 to 2021. From the accomplishment of this research, it was concluded that despite the high incidence of users of drugs of abuse there is still no pharmacological treatment defined for cocaine/crack-dependent individuals, therefore, it is necessary to carry out more studies on the subject in order to reduce the symptoms of withdrawal from substance use.